P09 The Use of Cochrane Reviews in Clinical Guidelines For Respiratory Disease in Children in the United Kingdom – a Systematic Review. (4th June 2013) - Cox, THN; Smyth, AR; Prayle, AP; Hughes, DA; Rycroft-Malone, J; Thomas, K
Abstract : Aims: Cochrane reviews (CRs) summarise best evidence and should be used for guideline recommendations. We assessed the use of CRs in UK guidelines for lower respiratory disease in children and the agreement between the guideline recommendations and the CRs. Methods: We searched Embase, Pubmed and the websites of guideline commissioning agencies for clinical guidelines. For each guideline recommendation, we identified relevant CRs in the Cochrane Library. We noted whether the CRs were cited in the guidelines and if they agreed with the guideline recommendations. Two investigators independently assessed CRs for relevance and agreement. We investigated the influence of the guideline commissioning agency and the topic, upon whether CRs were cited and whether their conclusions were followed. We investigated factors influencing the use of CRs, using logistic regression. Results: We identified 21 guidelines which made 1025 recommendations, of which 555 were recommendations for treatment of lower respiratory disease in children. For 115 of these 555 recommendations (21%) we identified a CR which could inform the recommendation. Approximately, one third of these recommendations (40/115) did not use any of the available CRs or used only some. The guideline commissioner had a significant influence on the use of CRs (p = 0.03), with BTS guidelines performing best. Guidelines on some topics eg cystic fibrosis were significantly more likely to cite CRs than others eg asthma (p = 0.007). In 20/115 guideline recommendations there was not full agreement with the CR Conclusion 9 (8%) disagreed, 6 (5%) partial agreement and 5 (4%) the guideline made a strong recommendation not supported by the CR. Conclusion: In spite of the work of the Cochrane collaboration, there are still many treatment decisions where there is no systematic review to inform guideline recommendations. However, we have shown that, even where a CR exists, guideline writers may not make use of it or may make recommendations contrary to the findings of the review. Guideline writers should describe their search strategy and reasons for not including high quality evidence.